Classroom Teacher Collaboration Strategies in Guidance and Counseling Services in Elementary Schools: A Qualitative Study in Padang City and Solok Regency - Meri Susanti; Neviyarni; Jemkhairil; Afnibar (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Guidance and counseling services in elementary schools are a crucial need because students are in a period of development. In elementary schools (SD), guidance and counseling services are carried out by class teachers. This condition requires class teachers to use the right strategy to establish collaboration with relevant elements, so that the services provided run effectively and efficiently. This study aims to identify and describe the collaboration strategies of classroom teachers in guidance and counseling services in elementary schools in the areas of personal, social, learning, and career development. The research method used is qualitative with a phenomenological approach, and in-depth interviews were conducted. The research informants were the head of the curriculum and elementary and secondary education students, the principal, and classroom teachers. The study found that guidance and counseling services in elementary schools were provided by classroom teachers. Various problems faced by students require intensive attention because they affect students' academic performance, especially those related to personal, social, and learning issues. To overcome these problems, appropriate strategies are needed that align with students' conditions and involve their families. Various problems faced by students require intensive attention because they affect students' academic performance, especially those related to personal, social, and learning issues. To overcome these problems, appropriate strategies are needed that align with students' conditions and involve good cooperation and mutual support among school personnel, principals, and parents. Keywords: collaboration strategies, guidance and counseling, classroom teachers, elementary schools Layanan bimbingan dan konseling di sekolah dasar merupakan sesuatu kebutuhan yang sangat krusial, karena mereka dalam masa perkembangan. Di Sekolah dasar (SD), layanan bimbingan dan konseling dilaksanakan oleh guru kelas. Kondisi ini menuntut guru kelas menggunakan strategi yang tepat dalam menjalin kolaborasi dengan unsur terkait, agar layanan yang diberikan berjalan secara efektif dan efisien. Penelitian ini menggunakan metode kualitatif, melalui wawancara secara mendalam. Informasi dikumpulkan pada Kasi kurikulum dan peserta didik pendidikan dasar dan menengah, kepala sekolah dasar, dan guru kelas. Dari hasil penelitian terungkap bahwa layanan bimbingan dan konseling disekolah dasar dilakukan oleh guru kelas. Berbagai persoalan yang dihadapi siswa memerlukan penanganan secara intensif karena berpengaruh terhadap akademik siswa, seperti masalah pribadi dan sosial. Untuk mengentaskan permasalahan ini diperlukan strategi yang tepat dan sesuai dengan kondisi siswa, dengan melibatkan kerjasama yang baik dan saling mendukung antar personal sekolah, kepala sekolah dan orang tua